Morphological transformation of hBMSC from 2D monolayer to 3D microtissue on low-crystallinity SF-PCL patch with promotion of cardiomyogenesis - Lo, Hsin-Yu; Huang, An-Li; Lee, Pei-Chi; Chung, Tze-Wen; Wang, Shoei-Shen (Journal of tissue engineering and regenerative medicine, 2018)
The effects of the stiffness of substrates on the cell behaviours of human bone marrow-derived mesenchymal stem cells (hBMSC) have been investigated, but the effects of the secondary structures of proteins in the substrates on the morphological transformation and differentiation of hBMSC have yet been elucidated. To investigate these issues, silk fibroin-poly(ε-caprolactone) SP cardiac patches of poly(ε-caprolactone; P), on which is grafted by silk fibroin (SF) with various β-sheet contents (or crystallinity) to provide various degrees of stiffness, were produced to examine the in vitro behaviours of hBMSC during proliferation, and cardiomyogenesis on the SP patches. β-sheet contents of SF from 20% to 44% (SP20 to SP44, respectively) were induced on patches, which were examined by attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy, and analysed using the Fourier self-deconvolution method. The stiffness of the SP patches, quantified by their Young's moduli and elasticities, increased with the crystallinity of the SF. During 3 days of proliferation, hBMSC migrated and morphologically transformed into 3D microtissues with diameters of approximately 150-200 μm on low-stiffness SP20 and SP30 patches, whereas 2D monolayers were observed on the SP37 and SP44 patches. The 3D microtissues/patch yielded more extensive in vitro cardiomyogenesis of hBMSC than the 2D cell monolayer with significantly higher expressions of all examined cardiac-specific proteins after induction by 5-aza. Notably, in vivo subcutaneously growing 3D microtissues on SP20 patches and a 2D monolayer on SP44 patches were preliminarily demonstrated in a rat model. Morphological transformations of hBMSC from a 2D monolayer to a 3D microtissue by low-stiffness SP cardiac patches, promoting cardiomyogenesis, provide a new opportunity for cardiac tissue engineering.